Downsizing a Baerveldt Glaucoma Implant For the Management of Persistent Postoperative Hypotony: A Case Series. Issue 11 (November 2019) - Mavrommatis, Maria A.; Dangda, Sonal; Sidoti, Paul A.; Panarelli, Joseph F.
Abstract : Purpose: The purpose of this study was to describe a surgical technique for treating persistent hypotony after Baerveldt glaucoma implant (BGI) surgery. Materials and Methods: The medical records of 10 patients with persistent postoperative hypotony who underwent truncation of one or both wings of a previously placed BGI, combined with external ligation of the tube using a polypropylene suture, were retrospectively reviewed. Results: All 10 eyes that underwent BGI truncation and placement of a single, external, nonabsorbable (polypropylene) tube ligature exhibited resolution of hypotony within 24 hours and resolution of choroidal effusions within the first 2 postoperative weeks. The median time interval between primary BGI surgery and truncation was 5 months (range, 1.5 mo to 8 y). Median postrevision follow-up time was 12 months (range, 5 mo to 16.2 y). The mean preoperative intraocular pressure (IOP) was 2.1±1.0 mm Hg, and the mean IOP rose to 29.2±13.9 mm Hg on postoperative day 1. Mean IOP at week 1, month 1, and month 3 was 20.5±10.4, 19.7±11.8, and 18.0±8.2 mm Hg, respectively, using an average of 1.4±1.4 glaucoma medications at postoperative month 3. Ligature release after BGI revision was performed in 9 (90%) of the 10 patients. The median time to ligature release was 1.5 months (range, 3 wk to 4 y). There was no recurrence of hypotony in any of these patients. At most recent follow-up, the mean IOP was 12.9±6.0 mm Hg on an average of 1.5±1.3 glaucoma medications. Five patients demonstrated improvement in visual acuity from their prerevision best-corrected visual acuity. Conclusions: Truncation of one or both wings of a BGI and complete closure of the tube with nonabsorbable, but releasable, suture ligature is an effective and safe method for reversing persistent postoperative hypotony while maintaining IOP control. Abstract : Supplemental Digital Content is available in the text.